Assessing the Reliability of Satellite-Derived Evapotranspiration Data Using Numerical Modified Penman Method at Citarum Watershed - Evi Anggraheni; Faris Zulkarnain; Pranita Giardini; Kintan Maulidina; Babag Purbantoro; Raisya Afifah; Anang Muchlis; Siswanto Siswanto; Andry Rustanto; Muhammad Dimyati; Ahmad Zubair; Triarko Nurlambang; Ratih Dewanti; Iqbal Putut Ash-Shidiq; Irma Susanti (Indonesian Journal of Geography, 2023)
Evapotranspiration is an essential part of water availability analysis and crop water needs that are useful to estimate irrigation water demand. Since discharge measurement stations are limited, the analysis of water availability is the most important part of water management planning. Citarum watershed is the biggest watershed in West Java, supplies raw water to Jakarta, the capital city of Indonesia. Modified Penman is the common equation to analyze evapotranspiration, which was developed by Food and Agriculture Organization (FAO) and modified for tropical areas. Evapotranspiration is one term of the water balance equation. To determine water losses, it is necessary to solve this equation. Another source of evapotranspiration data is provided by the Moderate Resolution Imaging Spectroradiometer (MODIS) satellite's standard product, MOD16A2. In order to used the evapotranspiration satelilite data to fullfill the lack of groud station data, the reliability of satelite data is needed. The objective of this study is to compares and analyzes the reliability of satellite evapotranspiration potential images with the numerical Modified Penman method at Citarum Watershed. Modified Penman is one of several methods that calculate the evapotranspiration potential based on climate data. MOD16A2 was used for simulation data, and Modified Penman was used for baseline data. The reliability of the two simulations was analyzed by the skewness percentage of each pixel and period. The distribution of percent skewness indicates the performance of satellite evapotranspiration on the Modified Penman that represents the actual condition. The sensitivity of satellites is greatly affected by local weather conditions.